Dental age estimation of Ajnala skeletal remains: A Forensic odontological study: Forensic odontological age estimation of Ajnala teeth (Bulletin of the International Association for Paleodontology, 2020)
The bones and teeth encrypt huge biological, chemical and molecular information about past life events of an individual. Teeth often survive almost all sorts of destructions and degradations and thus, help reconstruct individual life histories for comparatively longer periods of time than other human osseous remains. Dental attrition is the gradual and patterned loss of dental tissues during natural mastication which generally increases with the advancing age of an individual. In present study, three hundred eighty-nine (N=389) mandibular molars (176 first and 213 second) collected from Ajnala skeletal assemblage and having intact anatomical features were considered for age estimations on the basis of their attrition levels using the average attrition stage (ASA) method proposed by Li and Ji (1-2). Thousands of unknown human skeletal remains were excavated non-scientifically from an abandoned well found underneath a religious structure at Ajnala, a north Indian suburb. The written accounts mentioned that 282 Indian-origin soldiers of the colonial army were killed in August 1857 and their corpses were dumped into the said abandoned well due to socio-political situations and sanitary reasons leading to their immediate burial (3-4). The mean age of the remains was estimated be around 34.5 and 33.6 years from Ajmal et al (2) and Li and Ji (1) regression models, respectively. Preliminary anthropological, radiological, chemical and molecular results have also revealed that the recovered human remains belonged to adult males. Though attrition patterns are population-specific, the regression equations generated from dental attrition stages of Indian subjects are expected to provide more representative and valid age estimates of Ajnala skeletal remains. Present study findings may not be sufficient enough for accurate age estimates of Ajnala remains for forensic purposes; these estimates may help in corroborative reconstruction of bio-archaeological information about these skeletal remains and may support age estimated from other analytical methods.Keywords: Forensic Odontology, Dental Attrition, Average Stage of Attrition, Age estimation